DEVELOPMENT OF PEDAGOGICAL COMMUNICATION COMPETENCE AS AN IMPORTANT FACTOR OF TEACHERS’ PROFESSIONAL MASTERY - PULATOVA ODINAKHON KHAMIDOVNA (International Journal of Literature and Language Studies, 2026)
This article examines the role of developing pedagogical communication competence in the formation and improvement of teachers’ professional mastery. The purpose of the study is to reveal the essence of pedagogical communication competence, identify its structural components, and scientifically substantiate its influence on the effectiveness of pedagogical activity. The study employed methods of pedagogical and psychological literature analysis, comparative analysis, observation, generalization, and a systematic approach. The findings demonstrate that pedagogical communication competence plays a significant role in developing teachers’ communicative culture, reflective abilities, pedagogical cooperation, and effective interaction with students. The study concludes that it is necessary to improve methodological systems aimed at developing communicative competence within teacher education programs.